Hydro-Morphological Conditions of the Coastline Post-Construction of Sea Dikes in Pekalongan, Central Java - Ilham Safikri; Muhammad Zainuri; Aris Ismanto (Buletin Oseanografi Marina, 2025)
Pekalongan is one of the cities in Central Java affected by tidal flooding. Tidal floods occur due to sea level rise and land subsidence in Pekalongan, so far the tidal floods have had an impact on the community. Infrastructure damage and disruption of community activities are examples of the impact of tidal floods in Pekalongan. One of the government policies in overcoming tidal floods is to build sea walls along the coast of     Pekalongan. This policy will certainly have an impact on the morphological pattern of the coastal area. This study was conducted to determine the pattern of currents, waves, and sediment characteristics on the coast of Pekalongan after the sea wall. The analysis was conducted using current and wave modeling of delft-3d application. Sediment analysis was conducted by analyzing sediment grain size (Granulometry). The results show that currents and waves are influenced by seasonal winds that occur in Pekalongan. The dominant season in coastal Pekalongan occurs between December - January (West Season). Current conditions in the west season move with a speed of 0.2 -0.3 m/set moving eastward. West season wave conditions move with a height of 7.2 meters with a peak period of 7.2 seconds. While the sediment characteristics in Pekalongan are dominated by mud - sandy. From these sediment characteristics, it can be concluded that the influence of currents and waves of the west season can cause the distribution of sediments towards the east.